2021
DOI: 10.7441/joc.2021.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility As a Source of Competitive Advantage in Large Enterprises

Abstract: The competitive advantage of enterprises in the conditions of market economy is not generated merely by ensuring high quality products and services. Therefore, in their strategies, they need to involve elements such as corporate social responsibility. The aim of the paper is to identify the key sources of competitive advantage of large enterprises. In the empirical research, the hypothesis has been tested to determine if the application of corporate social responsibility by enterprises has a statistically sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 20 publications
0
38
0
3
Order By: Relevance
“…Almost 80% of CSR + companies agree that competition contributes to higher performance than other service providers and tourism companies (only 58.2%). This outcome is supported by a study that found that CSR is one of the crucial sources of competitive advantage for large businesses in the market (Marakova et al, 2021). Another study suggests that CSR strategies emerge from competitive forces (Dupire & M'Zali, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…Almost 80% of CSR + companies agree that competition contributes to higher performance than other service providers and tourism companies (only 58.2%). This outcome is supported by a study that found that CSR is one of the crucial sources of competitive advantage for large businesses in the market (Marakova et al, 2021). Another study suggests that CSR strategies emerge from competitive forces (Dupire & M'Zali, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…Las empresas exportadoras deben gestionar un elevado nivel de competitividad frente a sus similares. Precios accesibles y el cumplimiento de estrictos estándares de calidad ya no son un diferencial, sino más bien requisitos básicos para acceder y permanecer en los mercados internacionales (Marakova, Wolak y Tuckova, 2021). Las empresas necesitan adoptar estrategias distintas a las tradicionales para diferenciarse de sus competidores (Martos, Cortés y Jiménez, 2019).…”
Section: Introductionunclassified
“…Así, se destacan las aportaciones de Tan, Ho, Pidani y Goveravaram (2021) en las cuales se destaca la RSE como una inversión estratégica. Existe consenso de criterios al considerar a la RSE como una herramienta estratégica (Barić y Omazić, 2018;Flores, Vega y Chávez, 2016;Marakova et al 2021;Nyuur, Ofori y Amponsah, 2019;Rueda, 2017), o como una fuente para generar oportunidades en segmentos de mercado (Boubakary y Moskolaï, 2016;Porter y Kramer, 2006).…”
Section: Introductionunclassified
“…As a result, enterprises attempt to build their positive reputation by various methods and instruments. Social commitment is a major determinant of a positive reputation, an asset distinguishing an enterprise from its competitors, and thus a source of competitive advantage (Maráková et al, 2021).…”
mentioning
confidence: 99%
“…Factors employed by enterprises to gain competitive advantage in the market are the subject of many studies (Antczak et al, 2021;Maráková et al, 2021;Kuźmiński et al, 2020;Dědina and Šánová, 2013). The literature fails to offer detailed analyses of measures that differentiate choice of enterprise competitiveness sectors.…”
mentioning
confidence: 99%